Penguatan Keberagamaan Masyarakat Desa Bonto Bunga Kecamatan Moncongloe Kabupaten Maros - Khaerul Aqbar; Azwar Azwar; M. Kasim (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2023)
The Community Service Program (KKN) Batch V of STIBA Makassar students aims to increase Islamic knowledge and religious skills in the people of Bonto Bunga Village, Mocongloe District, Maros Regency. Implementation of activities begins with mapping problems and needs using SOAR analysis. After analyzing the problems and needs, work programs are then prepared according to the needs of the community as a form of community service (PkM). The stages of PkM activities include: the observation stage, the preparation stage, the implementation stage, the mentoring stage, and the evaluation stage. Some of the programs/activities that have been successfully implemented are: Al-Qur'an Teaching (Kindergarten/TPA, Youth, and Adult Levels), Teaching Activities in Schools, Spreading Al-Qur'an, and “Tabligh Akbar” Preparation for Ramadan. From these activities, the enthusiasm and support from elements of the village government, the majelis taklim, and the community for the activities was quite large. The community feels the benefits after participating in this KKN program, including an increase in knowledge, insight and religious skills. The sustainability of this program is in the form of further coaching for the community, especially for fathers and youth.